Islamic Education Curriculum Reformulation And Development - Burhan Burhan; Andi Irwandi; Nurwidyayanti Nurwidyayanti (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aims to analyze the reformulation and development of the Islamic education curriculum. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible websites such as Google Scholar and SINTA. Then the data were analyzed and checked for validity through data triangulation. The results of this study concluded that the reformulation of the Islamic education curriculum refers to the philosophy of Islamic education with four concepts, namely ideal curriculum, entitlement curriculum, supported curriculum, and implemented curriculum. Thus, the curriculum does not place students as subjects who prepare themselves for future life but must follow various things that are considered useful based on the needs of the child. The next steps for curriculum development include (1) identification of educational needs, (2) analysis and measurement of educational needs, (3) preparation of curriculum designs, (4) curriculum validation (trial and refinement), (5) curriculum implementation, and ( 6) curriculum evaluation. As a crystallization of the nation's cultural values, the curriculum must always be the concern of educational, social and cultural experts in capturing the pulse of culture that moves in all the pillars of old and modern culture.